Event Study: The Impact of DPR Demonstrations and Ministerial Reshuffle on IDX Stock Volatility - Pali, Fayza; Usman, Rudy; Erwinsyah; Masruddin, Masruddin; Mile, Yuldi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study analyzes the reaction of the Indonesian capital market to political events, namely the House of Representatives (DPR) demonstration on August 29, 2025, and the Minister of Finance reshuffle on September 8, 2025. The research is motivated by increasing political uncertainty that may affect stock market volatility, particularly the Composite Stock Price Index (IHSG). A quantitative event study approach was employed using Abnormal Return (AR) and Trading Volume Activity (TVA) as the main variables. The observation period covered 10 trading days, consisting of five days before and five days after the events. The sample included cross-sector companies listed on the Indonesia Stock Exchange, selected through purposive sampling. Secondary data on stock prices and trading volumes were analyzed using SPSS software. The results indicate no significant difference in abnormal returns before and after the political events, while trading volume activity shows a statistically significant difference. These findings suggest that political events have a greater impact on trading activity than on short-term stock price movements. This study contributes empirical evidence to event study research in Indonesia and provides insights for investors and policymakers in responding to political uncertainty in the capital market.